PENGARUH LAYANAN BIMBINGAN KELOMPOK TERHADAP PENINGKATAN LEADERSHIP RANTING IPM DI SMK MUHAMMADIYAH 2 PEKANBARU PERIODE 2014/2015 - Monica Safitri .M. Safitri; Zulfan Saam Saam; Tri Umari Umari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : The tittle of this research is the effect of guidance group towards the increasing of leadership of IPM branch. Purpose of this research is: 1. To know the leadership of IPM branch before implementing the guidance group services. 2. To know the process of implementation of guidance group services in order to increase the leadership of IPM branch. 3. To know the leadership of IPM branch after implementing the guidance group services. 4. To know the difference between before and after implementing the guidance group services to the leadership of IPM branch. 5. To know is there any influence in the implementation of the guidance group services to increase the leadership of IPM branch. This research used the quasi experiment method, by using one group pretest-posttest design. The subject of this research was members of the IPM branch at SMK Muhammadiyah 2 Pekanbaru, about to 30 peoples, by using random sampling techniques. To know the level of students’ leaders by using the questionnaires. Analysis of data using statistical techniques percentage, to distinguish the leadership of students’ between before and after implementing guidance services group t-test was used obtained tgreater bigger than ttable (10.92> 2.0) to the significant level of 5%. So Ho rejected and Ha accepted which means that in this research there is a difference to the improvement of the leadership before and after implementing guidance group services. And then from the product moment coefficient r = 0.53 determinant that is r2 = 0.28. Based on the results of research, it can be concluded that there is a significant increase after the implementation of the guidance group services of the leadership of IPM branch at SMK Muhammadiyah 2 Pekanbaru 2014/2015 period. Keywords : Guidance Group, Leadership